2021
DOI: 10.7759/cureus.14749
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Fever, Aphthous Stomatitis, Pharyngitis, and Cervical Adenitis Syndrome: A Rare Etiology of Fever in Adults

Abstract: We report the case of a 28-year-old male, with a past history of recurrent pharyngitis and tonsillectomy, who presented to the emergency department with fever, pharyngitis, and cervical adenitis. Inflammatory markers were elevated and the patient was initially started on ceftriaxone with remission after four days. However, the symptoms recurred three weeks later and an autoinflammatory disease was suspected. After exclusion of other illnesses, a diagnosis of periodic fever, aphthous stomatitis, pharyngitis, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Although the onset of the disease before the age of 5 is a mandatory criterion according to the modified Marshall’s criteria, there is an increasing number of papers reporting adult-onset PFAPA syndrome. 4 , 19 Hofer et al 12 reported that 10% of their patients that were classified as PFAPA patients based on expert opinion had disease onset after 5 years of age and the patients with late-onset disease showed similar clinical features compared with patients with disease onset before 5 years of age. Based on these findings, the authors suggested that age is not a reason for exclusion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the onset of the disease before the age of 5 is a mandatory criterion according to the modified Marshall’s criteria, there is an increasing number of papers reporting adult-onset PFAPA syndrome. 4 , 19 Hofer et al 12 reported that 10% of their patients that were classified as PFAPA patients based on expert opinion had disease onset after 5 years of age and the patients with late-onset disease showed similar clinical features compared with patients with disease onset before 5 years of age. Based on these findings, the authors suggested that age is not a reason for exclusion.…”
Section: Discussionmentioning
confidence: 99%
“… 2 , 3 Although the disease is commonly seen in childhood and resolves before the adolescent period, there is an increasing number of studies reporting the adult-onset PFAPA syndrome. 4 …”
Section: Introductionmentioning
confidence: 99%
“…This is the most common periodic fever condition in children with 90% of cases occurring before the age of 5 (pediatric onset). In recent times, increasing evidence suggesting a wider expression pattern of the disease has been pointed out, with disease onset in children over 5 years (late onset) and adults more common than initially suspected (2)(3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%